(untitled) (Repertorio Científico, 2024)
Introduction: The Remote Experimentation Laboratory (REL) was established in 2018 in response to the Universidad Estatal a Distancia (UNED) need to strengthen the development of experimental activities within the distance education model. Objective: This study aims to analyze the scientific productivity that the Remote Experimentation Laboratory has contributed to the final graduation projects in the fields of exact and natural sciences from 2018 to the present. Methodology: A review was conducted on two master’s theses and four undergraduate theses, applying an assessment methodology focused on research quality, with criteria such as credibility and internal validity, transferability, dependency-reliability, and objective conformability. Each criterion was evaluated based on specific dimensions and aspects